Newsletter No. 16 - (:unkn) unknown (My University, 2007)
The completion of Wave 2 data collection and details of Wave 3 development are available in the Autumn newsletter, as well as information on between waves contact, Life at 3, and presentations at upcoming conferences.
16
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology